O letramento literário nos anos finais do ensino fundamental com foco na ascensão da escola pública como mediadora da cultura letrada - Paula Helena Goulart Rodrigues (2016)
This action-research focuses on literacy, mediating literacy culture. I begin with the verification that over the final years of elementary school students lose the interest in reading literary texts. The evidence that the access to cultural goods, including literature, is still reserved for the elitist society, not coming to the popular classes, is another factor which I found very disturbing, as it is the target audience of this research is public school students. The Portuguese and Literature classes, as well as the reading projects developed in schools, have been insufficient to promote the habit of reading. In order to be the school the main institution responsible for the dissemination of cultural property, this action-research turns to the role of public schools in mediating literacy because it is up to it to ensure access to literature and to ensure the minimum conditions to students so that they can use it. To make it happen, it´s crucial that the Portuguese and Literature teachers provide the mediation of literary reading, support literacy and form the literary reader. Thus, this work aims to propose and implement reading activities of the literary text to 9th grade students of a public school in the city of Arcos, seeking to provide them with literacy, so that reading occurs in a dialogical process, where author and reader are meant builders, consolidating fluency and understanding readers, ensuring the formation of autonomous readers. By electing to work with Machado de Assis´ tales, I noted, above all, the refined language of the author, his care in aesthetic creation of the texts and the relevance of its themes. The selection of these tales took into account the age of the students and what their reading could provide them, both in terms of aesthetic enjoyment and in relation to advances in learning reading strategies. The work done with the tales A cartomante and Pai contra mae provided the development of diversified activities, prioritizing reading guided by the teacher in a constant reading of sharing work. When you report the completion of the activities, analyzing them, I can clearly see the students engagement with the narrative, their effective participation, the development of discussions that were exposed opinions and feelings. The preparation of the activities and the way they were conducted facilitated the understanding of the text, contributing to the individual and collective construction of meaning. So that there is formation of the literary reader, and indeed the students are able to perform the reading of a literary work, the proper education of the literary text makes is essential, and it is also indispensable the mediation of the teacher as a guide that teaches strategies, that forms the taste and leads to literary aesthetic enjoyment.